Interfacial Reaction of Sn-Ag-Cu Lead-Free Solder Alloy on Cu: A Review - Liu Mei Lee; Ahmad Azmin Mohamad (Advances in Materials Science and Engineering)
This paper reviews the function and importance of Sn-Ag-Cu solder alloys in electronics industry and the interfacial reaction of Sn-Ag-Cu/Cu solder joint at various solder forms and solder reflow conditions. The Sn-Ag-Cu solder alloys are examined in bulk and in thin film. It then examines the effect of soldering conditions to the formation of intermetallic compounds such as Cu substrate selection, structural phases, morphology evolution, the growth kinetics, temperature and time is also discussed. Sn-Ag-Cu lead-free solder alloys are the most promising candidate for the replacement of Sn-Pb solders in modern microelectronic technology. Sn-Ag-Cu solders could possibly be considered and adapted in miniaturization technologies. Therefore, this paper should be of great interest to a large selection of electronics interconnect materials, reliability, processes, and assembly community.